Stress-Free Surgery in Caudal Analgesia: A Literature Review - I Putu Kurniyanta; Tjokorda Gde Agung Senapathi; Gede Eka Wiratnaya; Ida Ayu Ika Wahyuniari; Jeremy Jonathan (Bali Journal of Anesthesiology)
Pediatric surgery patients require special consideration, as they are susceptible to surgical stress response. Stress response may increase detrimental hormonal and inflammatory mediators, leading to higher postoperative morbidity. Caudal analgesia has become essential in pediatric anesthesia due to its efficacy in pain control and stress response. The utilization of caudal analgesia in pediatric surgical patients has shown significant reductions in glucose levels during and after procedures. This technique effectively mitigates the hyperglycemic response typically associated with surgical stress. Furthermore, a caudal block may lower cortisol and prolactin plasma concentrations, contributing to a more favorable physiological state during the perioperative period. Caudal analgesia also plays a vital role in reducing pro-inflammatory markers due to surgical trauma. The reduction in inflammatory markers facilitates pain management and promotes faster recovery, resulting in less postoperative discomfort for pediatric patients.